Evaluation of fungicides, botanicals and non-conventional chemicals against brown spot of rice - D.S. DODAN, S. SUNDER*, RAM SINGH (Indian Phytopathology, 2010)
Among six fungicides evaluated, propiconazole (1 ml/l) and hexaconazole (2 ml/l) proved most effective and reduced the leaf spot severity from 22.34% to 5.19 & 7.98% and stalk rot incidence from 51.13% to 26.02 & 30.04%, respectively alongwith significant increase in grain yield of rice. Amongst 10 botanicals, Neemazal (3 ml/l) and Wanis (5 ml/l) provided about 26% reduction in leaf spot phase, and Neemgold, Achook, Tricure, Thuja leaves and garlic cloves reduced stalk rot incidence by 16 to 19%. Among nine non-conventional chemicals, ferric chloride, sodium salenate and nickel nitrate reduced both the phases of the disease considerably but the latter two chemicals had some phytotoxic effect on leaves.